Fictions of Knowledge
VIII, 247 p.
Keywords: Locating literature at the intersection of distinct areas of thinking on the nature, scope and methods of knowledge - philosophy, theology, science, and the law - this book engages with literary texts across periods and genres to address questions of probability, problems of evidence, the uses of experiment and the poetics and ethics of doubt.